The Impact of Down-Regulation on Obstetrics and Perinatal Outcomes in Singleton Pregnancies After In Vitro Fertilization - Jin, Lei; Ai, Jihui; Zheng, Yu; Chen, Biao; Wang, Lan; Dong, Xiyuan (Frontiers in Endocrinology, 2021)
Background: down-regulation has been widely used in IVF treatment; however, it lacks reports on the impact of down-regulation on obstetrics and perinatal outcomes. The purpose of this study was to compare the obstetrics and perinatal outcomes among different down-regulation conditions. Methods: this is a retrospective cohort study on 3578 patients achieving cumulative singleton clinical pregnancy after their first oocytes retrieval cycle. Patients were grouped according to the serum estradiol after down-regulation (E2D) into three groups: <30, 30-55, >55 pg/ml. The obstetrics and perinatal outcomes, and live-birth rate per clinical pregnancy were main outcome measures. In the subgroup analysis, patients were further divided according to the mode of transfer. ANOVA, chi-square test, multivariate logistic regression, and multivariate general linear model were performed for statistical analysis. Results: the patients with E2D <30, 30-55, >55 pg/ml had similar live-birth rates. The patients with E2D <30 pg/ml had a lower risk of hypertension disorders than those with E2D 30-55 pg/ml. No difference was found in the risks of placenta previa, placenta abruption, premature rupture of membrane, hemorrhage, gestational diabetes mellitus, or intrauterine growth restriction. The newborns in the group with E2D <30 pg/ml had a lower risk of PICU admission than those in the group with E2D >55 pg/ml. There was no difference in the risks of congenital anomalies or mortality among the three groups. No differences were found in the gestational week, percentages of preterm birth and very preterm birth, birth weight, percentages of low birth weight and very low birth weight, delivery mode, or sex of newborn. Subgroup analysis showed that E2D 30-55 pg/ml was associated with a higher risk of low birth weight in patients with one fresh transfer + frozen transfer(s). Conclusion: Down-regulation has no effect on the live-birth rate per clinical pregnancy. Patients with E2D <30 pg/ml may have advantages regarding lower risks of both maternal hypertension and newborn PICU admission. E2D 30-55 pg/ml may be associated with low birth weight in patients with relatively low quality embryos.